COVID-19 Vaccine Hesitancy and Acceptance in a Cohort of Diverse New Zealanders - Kate C. Prickett; Hanna Habibi; Polly Atatoa Carr (Elsevier, 2021)
Background: New Zealand's Immunisation Programme is an important pillar in the war against COVID-19, making high vaccine uptake essential. This study sought to: (1) identify potential vaccine uptake rates among New Zealanders prior to programme rollout; (2) understand reasons for unlikelihood/likelihood of vaccine uptake; and, (3) explore sociodemographic differences in risk of and reasons for vaccine hesitancy. Methods: Data were collected in March 2021 (n = 1,284) via a web-based survey. Respondents were a diverse sample of New Zealanders who were part of a large, pre-existing social research sampling frame. Multinomial and logit regressions were estimated to examine sociodemographic predictors of vaccine hesitancy and reasons for likelihood/hesitancy. Findings: Overall, 70% reported they would likely take the vaccine once available (i.e., very likely or somewhat likely). Being younger and less educated were correlated with greater vaccine hesitancy risk (i.e., very unlikely, somewhat likely, or unsure). Women were more likely than men to say they were unsure (Relative Risk Ratio = 1.60) vs. either likely or unlikely and to identify concerns regarding personal health, such as potential side effects, as a reason. Men identified concerns surrounding trust in vaccines and the perceived exaggerated risk of COVID-19 to them and the population. Interpretation: Although a majority intend to take the COVID-19 vaccine once available, a sizeable minority who were more likely to be young, female, and less educated, were unsure about or unlikely to get the vaccine, primarily due to perceptions of unknown future side effects. Ethnicity was not statistically associated with vaccine hesitancy, suggesting that public health efforts aimed at increasing vaccine acceptance among Māori and Pacific peoples-subgroups most at-risk of COVID-19 infection and morbidity-should focus on inequities in health care access to increase uptake.